Preliminary Validation of Self‐assessment Tool to Measure Imatinib Adherence in Patients with Chronic Myeloid Leukemia. Issue 2 (28th January 2013) - Daouphars, Mikael; Ouvry, Marine; Lenain, Pascal; Rouvet, Jean; Jardin, Fabrice; Bubenheim, Michael; Varin, Remi
<x xml:space="preserve">Abstract</x> Study Objectives To develop and validate a self‐assessment adherence tool for imatinib in patients with chronic myeloid leukemia (CML), and to correlate the use of this tool with response to treatment and adverse effects. Design Retrospective cohort study. Setting Regional cancer center in France. Patients Forty‐six patients with chronic phase CML treated with imatinib for 6 months or longer as of July 1, 2009. Measurements and main results We developed a self‐assessment questionnaire consisting of 10 questions to identify patients who were nonadherent to their cancer treatment. Each answer was worth 1 point, resulting in a possible maximum score of 10. The questionnaire was validated in patients receiving imatinib, using an objective adherence evaluation: a patient's score on the self‐assessment questionnaire was correlated with prescription refills, expressed as a medication possession ratio. A score of less than 8 was associated with a positive predictive value of 0.83 to have a medication possession ratio below 90%. With use of this questionnaire, half of the patients receiving imatinib would be identified as being nonadherent (sensitivity 0.5). Few adherent patients would be falsely identified as nonadherent, as the questionnaire's specificity was 0.97. Conclusion This self‐assessment questionnaire was validated for the first time in patients receiving imatinib for CML treatment. It provides a simple practical tool for health care professionals to assess patient adherence during their routine clinical practice and to propose targeted interventions for those identified as possibly nonadherent.